Caffeine Supplementation and muscle damage in soccer players - Marco Machado; Anselmo Carvalho Breder; Marcio Carvalho Ximenes; Jarbas Rodrigues Simões; José Fábio Florentino Vigo (Universidade de São Paulo, 2009)
The aim of this work was to evaluate the effect of caffeine supplementation and intermittent exercise on the muscle injury markers in soccer players. 15 male professional soccer players completed a placebo controlled double blind test protocol. 45 minutes before exercise, participants ingested 5.5 mg.kg-1 body mass of caffeine (EXP, n=8) or placebo (CONT, n=7). The exercise was 12 sets of 10 sprints (20 m each) with 10 sec recovery time between sprints and 2 min between sets. Blood samples were collected before (PRE) and 48h after exercise (POST). Serum activity of CK, LDH, AST, and ALT were quantified. Serum enzyme activity was enhanced by exercise in both groups, without a synergistic effect of caffeine. The findings suggest muscle injury markers concentration increases after physical activities, but caffeine supplementation (as used in this study) has no influence upon muscle cellular integrity. O objetivo do trabalho foi avaliar o efeito da cafeína e do exercício intermitente nos marcadores de lesão muscular em jogadores de futebol. 15 jogadores de futebol profissional completaram um estudo duplo-cego placebo controlado. 45 minutos antes do exercício, os participantes ingeriram 5.5 mg.kg-1 do peso corporal de cafeína (EXP, n=8) ou placebo (CONT, n=7). O exercício consistiu em 12 séries de 10 sprints (com 20 m cada) com 10 segundos de recuperação entre os sprints e 2 min entre as séries. Amostras de sangue foram coletadas antes (PRE) e 48h depois do exercício (POST). As atividades séricas de CK, LDH, AST e ALT foram quantificadas. A atividade sérica de todas as enzimas aumentou em ambos os grupos, sem efeito sinérgico da suplementação de cafeína. Os achados confirmam que o exercício aumenta a atividade sérica das enzimas, mas a cafeína (como a usada neste estudo) não interfere na integridade da fibra muscular.